OPTIMIZING THE PROCESSING OF HOUSEHOLD WASTE INTO COMPOST IN SUMBER BAKTI VILLAGE, NAGAN RAYA REGENCY - Muhammad Ikhsan; Sufriadi (RADJA PUBLIKA, 2022)
Garbage is a problem that must be overcome considering the negative impact it has on human health and the environment. The waste problem is also a challenge for the people of Sumber Bakti Village, because a lot of garbage is scattered around the village which has a negative impact on community health and the village environment. To minimize waste problems, there must be organic waste management which aims to be able to benefit from economic, social, sustainability and environmental insight. This waste optimization activity involved the Mawar Women Farmers Group of 30 people. starting from the stage of socialization to the stage of making organic fertilizer. The method used begins by distributing questionnaires to the Rose Farmers group, to find out the development of understanding and experience in utilizing household waste to become organic fertilizer and vegetable cultivation. This training activity on making compost and cultivating vegetables in a vertical manner was carried out in Sumber Bakti Village, Darul District, Nagan Raya Regency. As well as members of farmer groups can add knowledge in the use of household organic waste, as well as a much healthier environment, and can improve the economy.